Intensive Care and Treatment of Severe Guillain-Barré Syndrome - Pei Shang; Pei Shang; Jiachun Feng; Wei Wu; Hong-Liang Zhang (Frontiers Media S.A., 2021)
Guillain-Barré syndrome (GBS) is an acute polyneuropathy mostly characterized by acute flaccid paralysis with or without sensory/autonomous nerve dysfunction. Current immuno therapies including intravenous immunoglobulin (IVIg), plasma exchange (PE), and newly developed biological drugs benefit patients by alleviating hyperreactive immune responses. Up to 30% of patients develop respiratory failure during hospitalization and require mechanical ventilation and intensive care. Immunotherapies, mechanical ventilation, supportive care, and complication management during the intensive care unit (ICU) stay are equally emphasized. The most important aspect of intensive care and treatment of severe GBS, that is, mechanical ventilation, has been extensively reviewed elsewhere. In contrast to immunotherapies, care and treatment of GBS in the ICU setting are largely empirical. In this review, we intend to stress the importance of intensive care and treatment, other than mechanical ventilation in patients with severe GBS. We summarize the up-to-date knowledge of pharmacological therapies and ICU management of patients with severe GBS. We aim to answer some key clinical questions related to the management of severe GBS patients including but not limited to: Is IVIg better than PE or vice versa? Whether combinations of immune therapies benefit more? How about the emerging therapies promising for GBS? When to perform tracheal intubation or tracheostomy? How to provide multidisciplinary supportive care for severe cases? How to avert life-threatening complications in severe cases?